2018
DOI: 10.1186/s13012-017-0708-3
|View full text |Cite
|
Sign up to set email alerts
|

Objective coding of content and techniques in workplace-based supervision of an EBT in public mental health

Abstract: BackgroundWorkplace-based clinical supervision as an implementation strategy to support evidence-based treatment (EBT) in public mental health has received limited research attention. A commonly provided infrastructure support, it may offer a relatively cost-neutral implementation strategy for organizations. However, research has not objectively examined workplace-based supervision of EBT and specifically how it might differ from EBT supervision provided in efficacy and effectiveness trials.MethodsData come fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 59 publications
2
75
1
Order By: Relevance
“…In addition, respondents indicated that they spent an additional 1.5 hours per week on average in supervision focused on administrative content. These findings differ in total quantity and percentage of time devoted to clinical content when compared to previously reported findings of about 50 minutes every other week (Dorsey et al, 2018). Findings here suggest an adequate amount of supervision time as compared to NYS clinical licensing standards (New York State Education Department, 2017) or CT requirements for supervisory contact that require one hour per 40 hours of clinical contact (Supervision Competency Workforce Initiative, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, respondents indicated that they spent an additional 1.5 hours per week on average in supervision focused on administrative content. These findings differ in total quantity and percentage of time devoted to clinical content when compared to previously reported findings of about 50 minutes every other week (Dorsey et al, 2018). Findings here suggest an adequate amount of supervision time as compared to NYS clinical licensing standards (New York State Education Department, 2017) or CT requirements for supervisory contact that require one hour per 40 hours of clinical contact (Supervision Competency Workforce Initiative, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Elements of evidence-based, best practices in supervision have been articulated in the behavioral health literature and include observation of actual practice (i.e., live supervision with a supervisor providing feedback in vivo), use of direct observation or session recordings (Milne & Reiser, 2011), and use of client feedback and outcomes (Worthern & Lambert, 2007) to inform the supervision process. Despite the established utility and expectation of supervision, knowledge of best practice supervision availability for providers working in community mental health services remains limited (Dorsey et al, 2018). Evidence for supervision effectiveness is even less robust in non-behavioral health settings (e.g., child welfare) (Carpenter, Webb, & Bostock, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the back seat of this metaphorical tandem, the supervisee is therefore equally clearly depicted as a follower. A recent study examining workplace‐based supervision endorsed such leadership as crucial in driving CS outcomes (Dorsey et al., ).…”
Section: Leadership In Csmentioning
confidence: 99%
“…managing the session, agenda‐setting, teaching), relating these to linked ratings of the effect such behaviours have on the supervisee. Similarly, coding what is said in supervision (content evaluation) also appears promising as a methodology to evaluate feedback practices and leadership within CS (Dorsey et al., ).…”
Section: How Can Supervisors Become More Effective Leaders?mentioning
confidence: 99%